IMPACT-CABG Trial: Implantation of CD133+ Stem Cells in Patients Undergoing Coronary Bypass Surgery—Presentation of the First Treated Patient. (22nd June 2011) - Forcillo, Jessica; Stevens, Louis-Mathieu; Mansour, Samer; Prieto, Ignacio; Roy, Denis-Claude; Noiseux, Nicolas
Abstract : The IMPACT-CABG study is the first Canadian randomized-controlled phase II clinical trial aiming to assess the effect of intramyocardial (IM) injections of CD133 + -selected stem cells in patients referred for coronary artery bypass graft (CABG) with a "chronic" myocardial infarction and persistent left ventricular dysfunction. Patients are followed for 2 years with different imaging techniques including the stress magnetic resonance to evaluate the global and regional myocardial viability. Before the beginning of the randomization, the 5 first patients are treated in an open-label fashion to assess safety and feasibility of the IM CD133 + injections. Herein, we report the first Canadian patient treated with IM injection of CD133 + cells during CABG surgery as part of the IMPACT-CABG trial.